PENGARUH MOTIVASI BELAJAR, MOTIVASI ORANG TUA, DAN LINGKUNGAN BELAJAR TERHADAP PRESTASI AKADEMIK (Studi Empiris Mahasiswa Akuntansi di Malang) - Ayu Farida; Noor Shodiq Askandar; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study was to determine the effect of learning motivation, parental motivation and learning environment on academic achievement of accounting students in Malang which in this study was conducted on undergraduate accounting students majoring in 2017 at three (3) universities in Malang, namely the Islamic University of Malang (UNISMA), Widyagama University Malang (UWG) and Gajayana University Malang (UNIGA). This research is a descriptive quantitative research. Data collection techniques using a questionnaire. Samples were taken using a purposive sampling technique and using the Slovin formula to determine the minimum number of samples. The data analysis technique was carried out by testing data quality (validity and reliability), normality test, classical assumption test (multicollinearity and heteroscedasticity) and hypothesis testing (simultaneous test, R square and partial test) with multiple analysis techniques using SPSS 22 program. either simultaneously or partially, learning motivation, parental motivation and learning environment have no effect on academic achievement of accounting students in Malang. Keywords: learning motivation, parents motivation, learning environment, academic achievement.